Gifts from the Other Side: Thresholds of Hospitality and Morality in an Eastern Indonesian Town. Issue 3 (20th October 2013) - Erb, Maribeth
Abstract The town of Labuan Bajo in Western Flores, Eastern Indonesia has experienced rapid changes in the past decade, primarily associated with the development of tourism. This paper engages with the ideas of Jacques Derrida on hospitality and sovereignty, to explore the shifting landscapes of hospitality in this Manggaraian town. His musings on 'the question of the foreigner', the 'conditions' of hospitality, and the idea of the threshold are used to capture the way that hospitality is experienced as a struggle, as a contradiction, as an 'aporia'.